The Psychometric Properties of the Norwegian version of Edinburgh Postnatal Depression Scale (EPDS) - Hanssen-Bauer, Ketil; Welander-Vatn, Audun (PsykTestBarn, 2012)
Description: John Cox et al. developed and published the Edinburgh Postnatal Depression Scale (EPDS) in 1987. The Royal College of Psychiatrists (UK) has the copyright for EPDS. There are two Norwegian translations. The copyright holder has only approved the 2001 translation by Malin Eberhard-Gran. This translation procedure involved back translation and comparison with the English original version. The EPDS measures depressive symptoms in postnatal women. It is a self-rating scale which consists of ten questions and takes five minutes to score. Trained health personnel are qualified to use the scale. Literature search: We included 13 papers from 11 Norwegian studies, and four papers from four Swedish studies. We found no papers from Danish studies. Nine Norwegian papers reported EPDS mean scores and standard deviations for pregnant and/or postnatal women, one of which also reported these parameters for women neither pregnant nor postnatal. Psychometrics: The evidence for criterion validity is weak, because it is investigated in only one study (n = 310), and the psychometric properties of the reference standard (PRIME-MD) is unknown. The study showed that using an EPDS score ≥ 10 as a cut-off gave no false negatives. However, given a three per cent prevalence of major depression, the proportion of false positives is very high (81 %). EPDS has good construct validity, based on large correlation coefficients with the MADRS (r = 0.78) and the SCL-25 (r = 0.80). These properties were investigated in the same study (N = 310). Good internal consistency reliability (Chronbach’s α) was found in five studies: α mean = 0.83 (range 0.81–0.86). The sample sizes varied from 310 to 2816 (mean 1697) participants in psychometric studies. Good test-retest reliability was found in one study: r = 0.74; N = 310. Conclusion: The Norwegian version of the EPDS has good reliability, but validity is only investigated in one study that found weak diagnostic accuracy. There is a need for more studies on criterion validity comparing the Norwegian version of EPDS with the best possible diagnosis of depression.